Analisis Praktik Guru dalam Menggunakan Statistik Hasil Belajar untuk Merancang Pembelajaran Diferensiatif - Mia Audina Musyadad; Meilia Prehartanti; Rendi Atnanto; Ade Ismail Fahmi; Vina Febiani Musyadad (EduInovasi: Journal of Basic Educational Studies, 2025)
21st-century education demands that teachers not only teach but also analyze learning outcome data as a basis for designing adaptive and responsive learning. One prominent approach is differentiated learning, which requires teachers to understand differences in student abilities through data interpretation, including learning outcome statistics. This study aims to analyze in-depth the practices of teachers in using learning outcome statistics to design differentiated learning in grade V of SDN Adiarsa Barat II. This study used a qualitative approach with a case study method. Data collection techniques included in-depth interviews, participant observation, and documentation, which were analyzed descriptively and analytically. The results showed that teachers used grade data as the primary reference in grouping students based on learning outcomes. This practice was carried out simply and more intuitively than systematically. Nevertheless, there is a pedagogical awareness that statistical data plays a crucial role in developing learning strategies that are appropriate to students’ needs. Limitations in training and statistical literacy are major obstacles to optimizing this practice. This study provides implications for the importance of strengthening teacher capacity in data utilization and encouraging the formation of a data-driven school culture.